Limits on anomalous top quark gauge couplings from Tevatron and LHC data - Tonero, Alberto [UNESP]; Fabbrichesi, Marco; Pinamonti, Michele (Elsevier, 2015)
We review and update current limits on possible anomalous couplings of the top quark to W gauge bosons. We consider data from top quark decay (as encoded in the W-boson helicity fractions) and single-top production (in the t-, s- and Wt-channels). We find improved limits with respect to previous results (in most cases of almost one order of magnitude) and extend the analysis to include four-quark operators. We find that new physics is constrained to live above an energy scale between 430 GeV and 3.2 TeV, depending on the form of its contribution.
Keywords: Anomalous couplings; BSM physics; LHC; Top quark